-3(2x-4)+6=-6x+18

Simple and best practice solution for -3(2x-4)+6=-6x+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2x-4)+6=-6x+18 equation:



-3(2x-4)+6=-6x+18
We move all terms to the left:
-3(2x-4)+6-(-6x+18)=0
We multiply parentheses
-6x-(-6x+18)+12+6=0
We get rid of parentheses
-6x+6x-18+12+6=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 49x-20-9=2x+9 | | -2x^2+7x+(x-7)^2=2 | | 7-5x+9=5x | | 2/3x+1/4=1/6 | | m-24=4 | | -27=5y+3 | | 7x-8x+4=5x-3 | | 2(2x+1)=5x-1 | | 2(3x^2-7x+1)=4 | | (13x-15)-(9+6x)=—3 | | y=2(3y+7+5) | | 3n^2-0.75=360 | | 65+2x+45=180 | | 3n^2+0.75=360 | | 9n+4=360 | | 9n+4+3n^2-0.75=360 | | (9n+4)+(3n^2-0.75)=360 | | .89x+x=1682 | | -4(-6w+3)-7w=3(w-6)-6 | | v/2-3=9 | | 13=5(y+3)-7y | | (2x-9)/7=11 | | (5x+7)(3x-1)=4x-5 | | 18X^2-2x-86=0 | | (x)=-x+2 | | (x)=-x+2(-5) | | f2–5f–6=0 | | x*30/100=42 | | X+2/2=2x+1/4 | | x=1/3x-7/4 | | 7x+5(-3x-2)=34 | | 6(x-2)-2(x+1)=4 |

Equations solver categories